RESPONSIBILITIES OF LIMITED AND COMPLEMENTARY PARTNERS TO EMPLOYEE RIGHTS IF CV (COMMANDITAIRE VENNOOTSCHAP) DECLARES BANKRUPT - Lukman Hadi, Ahmad; Santoso, Budi (JCH (Jurnal Cendekia Hukum), 2024)
While conducting business, a CV (Commanditaire Vennotschap) may face bankruptcy (Suspension Payment of Debt). In the Suspension Payment of Debt processes, it is crucial to consider the rights of employees. Therefore, it is essential to understand the responsibilities of each partner in the Major Labour Laws and Bankruptcy Laws regarding employee rights if the CV goes bankrupt. This study utilized a normative legal research method to analyze legislation, focusing on the inventory of positive law, legal principles, legal doctrines, legal findings in concrete cases, and legal systematics using secondary data (literature studies such as books, journals, theses, and dissertations). A CV (Commanditaire Vennotschap) cannot go bankrupt because it is not a legal entity, but bankruptcy can occur at the partner level within a CV (Commanditaire Vennotschap). The employee rights of limited partnership hold a particular position. The Major Labour Laws prioritize the payment of employee wages in the event of a company bankruptcy, while the Bankruptcy Law and suspension payment of debt tend to prioritize payment for other creditors secured by the company assets. Although there is legal certainty that payment of employee wages is a priority claim of the bankruptcy estate, there is controversy over this priority due to the different provisions of the two laws.